2016
DOI: 10.3928/01484834-20161011-05
|View full text |Cite
|
Sign up to set email alerts
|

Concept Maps in Nursing Education: A Historical Literature Review and Research Directions

Abstract: Background: Although concept mapping was created in the early 1980s, research in nursing education first appeared in 1992. This literature review analyzes the impact of concept mapping in nursing education. Method: A total of 221 articles, books, and book chapters were reviewed on the topic of concept mapping in nursing education. Results: Results indicate that concept-mapping research progressed from the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 96 publications
0
29
0
Order By: Relevance
“…This tool helps facilitate understanding of conceptual relationships and the structure of knowledge. There is a rich history of concept mapping use and research in nursing education (Daley, Morgan & Beman, 2016). For example, concept maps have been used as an alternative approach to nursing care plans, (Black, Green, Chapin, & Owens, 2000), to promote critical thinking, (Daley, et al, 1999;Hicks-Moore & Pastirik, 2006;Yeo, 2014) and to advance interdisciplinary education (Bressington, Wells & Graham, 2011;Daley, Durning & Torre, 2016).…”
Section: Supporting Literaturementioning
confidence: 99%
“…This tool helps facilitate understanding of conceptual relationships and the structure of knowledge. There is a rich history of concept mapping use and research in nursing education (Daley, Morgan & Beman, 2016). For example, concept maps have been used as an alternative approach to nursing care plans, (Black, Green, Chapin, & Owens, 2000), to promote critical thinking, (Daley, et al, 1999;Hicks-Moore & Pastirik, 2006;Yeo, 2014) and to advance interdisciplinary education (Bressington, Wells & Graham, 2011;Daley, Durning & Torre, 2016).…”
Section: Supporting Literaturementioning
confidence: 99%
“…In a concept map, interrelated cases are indicated with shapes, lines and figures (Kaddoura, VanDyke, Cheng, & Shea-Foisy, 2016). Although it is a method that has been started to be used since the early 1980s, it was first used in nursing education in 1992 (Daley, Morgan, & Beman, 2016). This technique is used in clinical applications, case presentations and lectures in nursing education (Bayindir et al, 2015;Khrais & Saleh, 2017;Trevisani et al, 2016;Uslu et al, 2013).…”
Section: Concept Mapmentioning
confidence: 99%
“…In addition, students gained a greater understanding of the complexity of clients' situations and why their problems were so difficult to resolve. Daley, Morgan, and Black Beman (2016) identified that while concept mapping has been used in nursing education for the past two decades, there are gaps in the literature related to applying concept map scoring formulas, and, creating concept map-centered learning environments. There is currently no literature available that describes the use of concept mapping to evaluate student learning in a community health nursing theory course, or that used the population health promotion model (PHPM) (Flynn, 1999).…”
Section: Background Literature On Concept Mappingmentioning
confidence: 99%